Genocide in the 20th century: with emphasis on the Bosnian and Rwandan genocide / Nurul Nabila Zamri and Putri Nurul Ain Mohd Adzmi - Zamri, Nurul Nabila; Mohd Adzmi, Putri Nurul Ain (2008)
This research project is regarding the crime of genocide. The focus of the research project is the Bosnian and Rwandan genocide. Assessment on both genocides was made carefully in order to understand what took place in both incidences. While the focus was on Rwanda and Bosnia, discussion on the genocide in Armenia, Nanking and Germany is studied briefly. The concentration of this research project is the limitations and legal constraints in prosecuting the crime of genocide. The limitations are regarding addressing genocide, prosecuting the perpetrators and jurisdiction as well as sovereignty. Throughout this research project, we have understood the happenings of the Bosnian and Rwandan genocide which is to understand why it took place. Furthermore, we were able to achieve our goals by examining the difficulties in prosecuting the crime of genocide. The objectives of this research project has been fulfilled especially in understand why genocide occurs and the reason behind the difficulties in prosecuting it.